The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.29082/ijnms/2017/vol1/iss1/41
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cognitive Behaviour Therapy to Decrease the Level of Depression for Leprosy Sufferer

Abstract: Leprosy is the ill that caused by mycobacterium leprae bacteria, which caused complex problem for leprosy sufferer. It gives bad effect in some aspects such as physic, social, economy, and psychology.  Psychologically, the leprosy sufferer gets the problem because of too much stigma to leprosy by society. Consequently, the leprosy sufferer stands aloof from the others, he feels shy, and gets depression. One of non-pharmacology treatment that can decrease the level of depression is Cognitive Behavior Therapy. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Through effective communication applications in disease management, leprosy patients are able to show good self-concepts [ 74 76 ], reduce negative emotional responses [ 77 ], high motivation to recover [ 78 ], open about her illness [ 42 ], increase self-confidence [ 79 ], and other family members are able to provide adequate care assistance [ 38 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through effective communication applications in disease management, leprosy patients are able to show good self-concepts [ 74 76 ], reduce negative emotional responses [ 77 ], high motivation to recover [ 78 ], open about her illness [ 42 ], increase self-confidence [ 79 ], and other family members are able to provide adequate care assistance [ 38 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This therapy improved the adaptation level of the participants from 92% to 96%. In another study by Rahmawati and Yuniarti (2017) CBT was used with 25 leprosy-affected persons dealing with depression. Study results showed that after the intervention depression rates lowered with 12% (Rahmawati and Yuniarti, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There were few universal findings, mainly because of the scarcity of studies conducted and the variety in the types of interventions and outcomes employed. However, all but two of the 14 studies reported positive mental health outcomes, including improvements in the psychological domains of quality of life for leprosy (87,146), Buruli ulcer (144), and tungiasis (39) [though two studies reported no improvements in the psychological aspects of quality of life (145,147)]; reduced depression symptoms for leprosy (87,93); reductions in anxiety levels and improvements in self-efficacy and self-concept for leprosy (117,148,150); lessened burden of leprosy (149); decreased cognitive and other disabilities for LF (151); improvements in patient information, patient-staff interactions, problem-solving, and reduced patient concerns for Buruli ulcer (122); and improvements in mood for nodding syndrome (85).…”
Section: Evidence For Interventions To Address Mental Illness Associa...mentioning
confidence: 99%